Comparative Transcriptome Analysis of the Key Genes Associated With the Accumulation of Lycorine And Glanthamine in Lycoris Aurea - Xiang, Xiaoliang; Jiang, Xia; Hu, Zhaotun; Tang, Jiuxin; Quan, Miaohua (Bangladesh Journal of Botany, 2022)
Lycoris aurea (L. aurea) can synthesize secondary metabolites, known as lycorine and galanthamine. Despite its pharmaceutical significance, the molecular mechanism underlying the accumulation of these medicinal components in L. aurea remains largely unexplored. Two populations of L. aurea (Hunan and Guangxi) with different contents of lycorine and galanthamine were selected for de novo RNA sequencing. A total of 337,746 unigenes were obtained, and 55,910 unigenes were differentially expressed between the two populations, consisting of 38,429 up-regulated and 17,481 down-regulated unigenes. Furthermore, expression pattern analysis showed that there were five differentially expressed genes involved in the biosynthesis of lycorine and galanthamine. Among them, tyrosine decarboxylase was significantly up-regulated, and it might be responsible for the differential accumulation of lycorine and galanthamine in different populations of L. aurea. Our findings provided new insights into the mechanism underlying the accumulation of lycorine and galanthamine, enriching the genetic resources for L. aurea breeding programs. Bangladesh J. Bot. 51(4): 767-777, 2022 (December)